وظيفة الجمارك الخضراء في حماية البيئة........ تجربة جمارك وحماية الحدود الأمريكية - حليس, عبدالقادر (جامعة الوادي - University of Eloued, 2023)
In this paper, we examine the Green Customs Initiative, which is based on strengthening the capacity of customs authorities and their partners to detect and combat illegal trade in contaminated goods. This transition can be achieved through balanced actions with respect to revenue collection, protection of society and facilitation of legal trade. Although these core Customs competencies make a vital contribution to supporting sustainable economic growth and development, Customs’ role has been redefined over recent years with even greater stress now being placed on the importance of its contribution to sustainable development. U.S. Customs and Border Protection (CBP) embraces the concept of promoting conservation of the earth’s natural resources. CBP aims to implement national security mission while moving toward a more sustainable future by both leading and supporting an array of initiatives.
The Function of Green Customs in Environmental Protection… U.S. Customs and Border Protection Experience
مقال
Keywords: الجمارك الخضراء ; التجارة الخضراء ; التنمية المستدامة ; امريكا; Customs, Green Customs, Green Trade, Sustainable Development Goals.